Assessing the need for traffic signalization from the perspective of local government units - Amistad, Franklyn T. (2006)
It is a fact that some cities in the Philippines are confronted with traffic problems brought about by the uncontrollable growth of population and the transportation system. And despite all the engineering efforts of the local government units to address the traffic problems of the different cities of Metro Manila, traffic problems such as road accidents, congestion, pollution, and energy problems still confront them. This study focuses on assessing the need for traffic signalization from the perspective of local government units (LGUs). The information revealed in this study is based on the perspective of the 23 LGUs or 23% of the 98 LGUs outside Metro Manila through key informant interviews.